Design and Build an IoT-Based Door Locking System Using Google Assistant - Diky Jaswa; Achmad Fauzi; Milli Alfhi Syari (PT. Inovasi Teknologi Komputer, 2023)
Home security is very important in everyday life. Frequent theft at home can make owners feel anxious. One of the factors causing theft is negligence in locking the door of the house and weaknesses in the security system used. Generally, homeowners still rely on manual door locks which are vulnerable to burglary, and often forget to put the key. To improve security, a better security system is needed. This research proposes the application of Internet of Things (IoT) technology to overcome this problem. The aim of this research is to implement IoT in a home door control system using voice commands via Google Assistant. This way, homeowners can lock and unlock doors remotely, which increases home security and reduces the risk of theft. This research designs a prototype control system that can be applied to the door lock concept and controlled using Google Assistant. The use of the NodeMCU module in this research allows an internet connection to control the door of the house efficiently. The research results prove that by using the NodeMCU Module and other devices the IoT system can be implemented, so that locking the door with the IoT system can be successfully carried out